Reactive oxygen species inhibit biofilm formation of Listeria monocytogenes. (February 2019) - Guo, Liang; Zhang, Chao; Chen, Guowei; Wu, Man; Liu, Wukang; Ding, Chengchao; Dong, Qingli; Fan, Enguo; Liu, Qing
Abstract: Although the level of reactive oxygen species (ROS) is altered upon the formation of bacterial biofilm, the relationship between ROS alteration and biofilm formation is still unclear. The aim of the present study is to use Listeria monocytogenes ( L. monocytogenes ) as a model organism to examine whether ROS have an effect on the biofilm formation. After eliminating ROS by treatment with NAD(P)H oxidase inhibitor Diphenyleneiodonium chloride (DPI) or scavenging reagents N-acetylcysteine (NAC), the biofilm formation of L. monocytogenes was examined. Our data demonstrate that DPI and NAC induced-reduction of ROS enhances the biofilm formation in L. monocytogenes without affecting bacterial growth and activity. These data provide the evidence that ROS produced by L. monocytogenes inhibit the biofilm formation. Highlights: Diphenyleneiodonium chloride (DPI) and N-acetylcysteine (NAC) did not affect the growth and activity of L. monocytogenes. DPI and NAC reduced the ROS production. ROS could inhibit the biofilm formation of L. monocytogenes.